Effects of Salvia miltiorrhiza active compounds on placenta-mediated pregnancy complications - Kong, Jingyin; Li, Songjun; Li, Yingting; Chen, Min (Frontiers in Cell and Developmental Biology, 2023)
Placenta-mediated pregnancy complications (PMPCs), including preeclampsia (PE), fetal growth restriction (FGR), and recurrent spontaneous abortion (RSA), occur in approximately 5% of pregnancies and are caused by abnormal placenta development. Developing effective therapies for PMPCs is challenging because of the complicated pathogenesis, such as disrupted vascular homeostasis and subsequent abnormal placentation. Synthetic drugs have been recommended for treating PMPCs; however, they tend to cause adverse reactions in the mother and fetus. Salvia miltiorrhiza (S. miltiorrhiza) has potential effects on PMPCs owing to its advantages in treating cardiovascular disorders. S. miltiorrhiza and its active compounds attenuate the symptoms of PMPCs through anticoagulation, vasodilation, antioxidation, and endothelial protection. Thus, in this review, we summarize the literature and provide comprehensive insights on S. miltiorrhiza and its phytochemical constituents, pharmacological activities, and their functions on PMPCs, which would be helpful for us to explore promising drugs.